ANALISIS PERENCANAAN ANGGARAN DAN REALISASI ANGGARAN PEMERINTAH DAERAH KABUPATEN MALANG TAHUN 2016-2018 - Wilis Auliana; Moh. Amin; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThe Purpose of This Research The purpose of this study was to analyze the performance of the Malang Regency Government Revenue and Expenditure Budget in 2016-2018 in financial terms and measured from the Budget Realization Report. This type of research used in this research is descriptive type of research. Descriptive research is research about a particular phenomenon or population that researchers obtain on the subject which is conducted to find out the independent variables, either one or more independent variables without making comparisons or connecting with other variables. The analytical method used in this study uses descriptive analysis based on the Budget Financial Report (LRA), namely the concept of the budget, especially the analysis of budget planning and budget realization. Data obtained directly from the BAKD Office. The results of this study Malang Regency Government said to be good in carrying out financial performance, but only a few evaluations that must be improved in managing decentralization, PAD, and income differences. The performance of the Malang Regency Government's APBD in allocating its Shopping Budget is said to be efficient, not indicated budget waste. Realization of Malang Regency Government Budget for 3 years running effectively by presenting the Budget Realization Report (LRA) in accordance with applicable procedures. Keywords: Budget Planning, Budget Realization, APBD Performance